The Role of Ahad Sholih Activities in Developing Children’s Noble Character - Nada Fadhilah; Tuti Alawiyah; Rahmat Rifai Lubis (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2026)
This study explores the role of the Ahad Sholih program at Masjid Istiqamah in Candirejo as a nonformal Islamic education initiative aimed at shaping children’s Noble Character. Conducted routinely every Sunday since 2020, the program engages children aged 4–12 years in structured activities including prayer, recitation of Asmaul Husna, memorization of daily supplications, short hadiths, and lessons on manners. Findings indicate that the program significantly contributes to moral development across three dimensions: fostering devotion to Allah through consistent worship practices, cultivating self-discipline, honesty, and confidence, and nurturing respect and responsibility toward others through social interaction and family engagement. The mosque environment provides a supportive religious atmosphere, while habituation methods and exemplary role modeling by instructors reinforce value internalization. Supporting factors include enthusiastic participation, effective teaching strategies, strong backing from mosque administrators, and parental involvement. However, challenges such as limited parental engagement, children’s short attention spans, resource constraints among mosque staff, and external factors like weather conditions were identified. Overall, Ahad Sholih demonstrates the effectiveness of mosque-based non formal education in instilling Islamic values and offers a replaceable model for other communities. Strengthening collaboration between families, mosque leaders, and educators is essential to maximize its impact on children’s moral and spiritual growth.